2020
DOI: 10.1101/2020.12.19.20248555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Healthcare worker intentions to receive a COVID-19 vaccine and reasons for hesitancy: A survey of 16,158 health system employees on the eve of vaccine distribution

Abstract: Healthcare workers (HCWs) have been recommended to receive first priority for limited COVID-19 vaccines. They have also been identified as potential ambassadors of COVID-19 vaccine acceptance, helping to ensure that sufficient members of a hesitant public accept COVID-19 vaccines to achieve population immunity. Yet HCWs themselves have shown vaccine hesitancy in other contexts and the few prior surveys of U.S. HCW intentions to receive a COVID-19 vaccine report acceptance rates of only 28% to 34%. However, it … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The second event was the release of phase III clinical trial results by two vaccine manufacturers, after which both vaccines were approved for Emergency Use Authorization (EUA). Similar results were found by Meyer et al (2020): an increase in daily recorded cases of vaccine willingness was reported after the EUA release.…”
Section: Discussion Ijns Manuscript Template (August 2021)supporting
confidence: 86%
“…The second event was the release of phase III clinical trial results by two vaccine manufacturers, after which both vaccines were approved for Emergency Use Authorization (EUA). Similar results were found by Meyer et al (2020): an increase in daily recorded cases of vaccine willingness was reported after the EUA release.…”
Section: Discussion Ijns Manuscript Template (August 2021)supporting
confidence: 86%
“…Repeated polls report that vaccine hesitancy has dropped over time (yet remains higher among Blacks) [ 25 , 31 ]. Surveys of health care workers reported more hesitancy (than the public) at the beginning of the pandemic, but as the results from clinical trials were released, hesitancy diminished precipitously [ 36 , 37 ]. Despite these promising trends, vaccine hesitancy may persist among historically marginalized populations unless substantial resources, funding, messaging, public health activities, and access to vaccination programs are deployed and evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…31,39 Surveys of health care workers reported more hesitancy (than the public) at the beginning of the pandemic, but as the results from clinical trials were released, hesitancy diminished precipitously. 40,41…”
Section: Discussionmentioning
confidence: 99%